Modern Times of the Civil and Economic Society - Vlaikov, Stoyan (Research Papers, 2016)
In this study paper the author elaborates on the theme of civil society in present days. He reveals the essence of the civil society, its typical signs and its conflict interaction with the Body politic. Also interpreted is the question of Economic society, which is a structural part of civil society. The Economic society expresses the interests of and defends the small and middle business, agriculture and commercial firms, and some other private enterprises. At the end, the author describes the values and the worth system of Civil society